Training at moderate altitude improves submaximal but not maximal performance-related parameters in elite rowers - Cerda-Kohler, Hugo; Haichelis, Danni; Reuquén, Patricia; Miarka, Bianca; Homer, Mark; Zapata-Gómez, Daniel; Aedo-Muñoz, Esteban (Frontiers in Physiology, 2022)
Maximal oxygen consumption (V̇O2max), physiological thresholds, and hemoglobin mass are strong predictors of endurance performance. High values of V̇O2max, maximal aerobic power (MAP), and power output at anaerobic thresholds are key variables in elite rowers. Endurance athletes often use altitude training as a strategy to improve performance. However, no clear evidence exists that training at natural altitude enhances sea-level performance in elite rowers. This study aimed to evaluate the effect of altitude training on rowing-performance parameters at sea level. The study was conducted on eleven rowers (6 females, 5 males) from the Chilean national team during a 3-week moderate altitude training (~ 2900 m.a.s.l.) under the live high-train high (LHTH) model. It included a rowing ergometer maximal incremental test and blood analysis (pre and post-altitude). Gas exchange analysis was performed to measure V̇O2max and physiological variables such as ventilatory thresholds (VTs) and rowing economy/efficiency (ECR/GE%). LHTL training improves performance-related variables at sea level (V̇Emax: 3.4%; hemoglobin concentration ([Hb]): 4.3%; hematocrit (%): 4.7%; RBC (red blood cells) count: 5.5%; power at VT2: 6.8%, V̇EVT2: 7.2%; power at VT1: 7.5%, V̇EVT2: 10.1%) and economy/efficiency-related variables (ECRVT2: -5.1%; ECRVT1: -3.5%; GE: 5.7%). The LHTH training decreased breathing economy at MAP (-3.1%), pVT2 (-9.6%), and pVT1 (-10.0%). Non-significant changes were found for V̇O2max and MAP. This study is the first to describe the effects of a 3-week moderate altitude (LHTH training) on performance and economy/efficiency-related variables in elite rowers, suggesting that it is an excellent option to induce positive adaptations related to endurance performance.